Odd clipping optical orthogonal frequency division multiplexing for VLC system. (2nd September 2019) - Ibrahim, Asmaa; Ismail, Tawfik; Elsayed, Khaled; Darweesh, M. Saeed
Summary: The Orthogonal Frequency Division Multiplexing (OFDM) has emerged as one of the promising techniques because of its robustness to multipath fading with high‐speed data transmission. Classical bipolar OFDM cannot be used in intensity modulated with direct detection (IM/DD) optical communication systems, as visible light communication (VLC), so many optical modulation techniques as asymmetrical clipped optical OFDM (ACO‐OFDM) and DC‐Clipped OFDM (DCO‐OFDM) have been investigated. In this paper, we introduce a novel optical modulation scheme that meets the optical communications requirements. The proposed odd clipping optical OFDM technique (OCO‐OFDM) is based on the Fourier transform symmetry properties in which the imaginary and odd signal is converted to odd and real valued signal. As a result of this work, the proposed OCO‐OFDM and its modified version have several benefits over ACO‐OFDM and DCO‐OFDM. By introducing a better bit error rate, with the same spectral efficiency as DCO‐OFDM and the same power efficiency as ACO‐OFDM for real valued modulation technique as Binary Phase‐Shift Keying (BPSK), and with the same spectral efficiency and power efficiency as ACO‐OFDM for complex valued modulation technique as Quadrature Phase‐Shift Keying (QPSK) and Eight Phase‐Shift Keying (8PSK). Abstract : In this paper, an odd clipped optical OFDM (OCO‐OFDM) and (MOCO‐OFDM) based on FFT replaces Hermitian symmetry by odd symmetry of Fourier transform, which states that the output of the IFFT is a pure real, and odd signal for pure imaginary odd input is proposed. The main contribution of this work is to develop and analyze a new OFDM modulation technique called OCO‐OFDM with low complexity and better performance compared with ACD‐OFDM and DCO‐OFDM.